MEDICAL VS SURGICAL TREATMENT FOR SYMPTOMATIC ENLARGED INFERIOR TURBINATE: A COMPARATIVE STUDY - Rehman, Habib -Ur-; Wahid, Fazal -I-; Zada, Bakht; Javaid, Muhammad; Haq, Naseem Ul (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the nasal patency after reducing the size of hypertrophied inferior turbinate with medication and surgery. Study Design: Prospective comparative study. Place and Duration of Study: Department of Ear, Nose, Throat, Head and Neck Surgery, Medical Teaching Institute, Lady Reading Hospital, Peshawar Pakistan, from Jan to Dec 2019. Methodology: This study was conducted at the After-sample size calculation using an online sample size calculator (OpenEpi) and after obtaining informed consent patients were divided into two groups. Patients in group A were put on medicine only and in group B surgery was conducted to reduce the size of hypertrophied inferior turbinate. Data were analyzed using SPSS version 25 and p<0.05 was considered significant. Results: This study comprised of total 86 patients, in the age range 15-55 years with mean ± SD age 33.47 ± 9.57 years. Males were 47 (54.7%) and females were 39 (45.3%) with male to female ratio of 1.2:1. In group A, males were 22 (25.25%), females were 21 (24.41%), while in group B males were 25 (29.1%) and females were 18 (20.3%). There was no statistically significant difference in nasal patency between the two groups before treatment (p=0.59) and after 10 days of treatment (p=0.69). However, at the end of one month, there was a statistically significant difference in nasal patency between the medically treated and surgically treated groups of patients (p=0.023). Conclusion: Surgical treatment is significantly effective than medical treatment alone.